L’esegesi di Cant 1,5-6 e il tema dell’epektasis in Gregorio di Nissa, con specifico riferimento al ruolo della grazia e del libero arbitrio - Marone, Paola (Vox Patrum, 2023)
As Moreschini rightly pointed out (Gregorio di Nissa, Omelie sul Cantico dei Cantici, a cura di C. Moreschini, Roma 1996, Intr. p. 9), Gregory of Nyssa’s Homilies on the Song of Songs «sono costruite sullo schema dell’epektasis», and it is no exaggeration to say that «esse vogliono rappresentare una serie di esperienze successive dell’anima la quale, dopo avere avuto un contatto, sia pure parziale, con lo sposo divino, approfondisce sempre di più il suo rapporto spirituale con lui». But above all about the exegesis of Ct. 1: 5-6 (I am dark, but lovely, You daughters of Jerusalem, Like Kedar’s tents, Like Solomon’s curtains. Don’t stare at me because I am dark, Because the sun has scorched me…) the epektasis is placed in a wide-ranging context and takes on a new meaning in a soteriological perspective. Hence the purpose of the present study is to analyze specifically the Homilies 2 and 4, concerning the exegesis of Ct. 1: 5-6, and to focus on all the theological topics (the gratuity of grace, the free acceptance of the gift of grace) with which Nyssen, now at the end of life, attributed the spiritual progress of the soul to the saving action of God, in accordance with what he had claimed, many years earlier, in De virginitate 12 («In fact this likeness to the divine is not our work at all…; it is the great gift of God bestowed upon our nature at the very moment of our birth»).